Elevated symptoms of executive dysfunction predict lower adaptive functioning in 3‐year‐olds with autism spectrum disorder. Issue 7 (6th April 2022) - Powell, Kelly; Macari, Suzanne; Brennan‐Wydra, Emma; Feiner, Hannah; Butler, Maureen; Goncalves Fortes, Diogo; Boxberger, Alexandra; Torres‐Viso, Mariana; Morgan, Chelsea; Lyons, Megan; Chawarska, Katarzyna
Abstract: Executive functioning (EF) deficits co‐occur frequently with autism spectrum disorder (ASD) and have a long‐term detrimental impact on quality of life of children and their families. Timely identification of risk for EF vulnerabilities may hasten access to early intervention and alleviate their long‐term consequences. This study examines (1) if EF deficits are elevated in toddlers with ASD compared to nonautistic siblings of children with ASD, typically developing (TYP) toddlers, and toddlers with atypical developmental presentation; and (2) if EF deficits have a detrimental effect on adaptive functioning in ASD. Participants were recruited between September 2014 and October 2019 and included 73 toddlers with ASD, 33 nonautistic siblings of children with ASD, 35 toddlers with atypical development, and 28 TYP toddlers matched on chronological age (M = 39.01 months, SD = 3.11). EF deficits were measured using the BRIEF‐P; adaptive skills were measured using the VABS‐II. Whenever appropriate, analyses were controlled for MSEL verbal and nonverbal developmental quotient, ADOS‐2 autism severity scores, and sex. Analyses revealed that toddlers with ASD exhibited elevated BRIEF‐P scores across all domains compared to each of the three comparison groups. Higher BRIEF‐P scores were associated with lower adaptive social, communication, and daily living skills while controlling for symptom severity, verbal and nonverbal functioning, and sex. In conclusion, marked vulnerabilities in EF are already present in 3‐year‐old toddlers with ASD and are predictive of the level of adaptive functioning in ASD. EF vulnerabilities in toddlers should be targeted for intervention to improve long‐term outcomes in ASD. Lay Summary: Many children with autism experience vulnerabilities in executive functioning (EF), which may include challenges with inhibition, working memory, cognitive flexibility, and planning. The study shows that these vulnerabilities can already be detected at age three and that their presence is linked with lower social, communication, and daily living skills. Screening children with ASD for EF challenges and helping those who have difficulties may improve their long‐term outcomes.